2001
DOI: 10.1038/sj.leu.2402203
|View full text |Cite
|
Sign up to set email alerts
|

Induction of graft-versus-leukemia to prevent relapse after partially lymphocyte-depleted allogeneic bone marrow transplantation by pre-emptive donor leukocyte infusions

Abstract: In this prospective study we analyzed pre-emptive donor leukocyte infusions (DLI) in 82 consecutive patients transplanted with partially T cell-depleted grafts for acute myeloid leukemia, acute lymphoid leukemia, chronic myeloid leukemia, refractory anemia with excess of blasts, refractory anemia with excess of blasts in transformation and multiple myeloma. Donors were HLA-identical siblings. Patients without significant acute (Ͼgrade 1) and/or chronic GVHD were scheduled to be treated with DLI (35 patients) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…This has been implemented with some success, particularly in high-risk patients treated with T-cell depleted (TCD) conditioning regimens. [31][32][33][34][35] Immunosuppressant therapy is tapered rapidly and DLI commenced early (1-6 months) and then stopped when a degree of GvHD is present or when a set cell dose is reached.…”
Section: Predicting and Preventing Relapsementioning
confidence: 99%
See 1 more Smart Citation
“…This has been implemented with some success, particularly in high-risk patients treated with T-cell depleted (TCD) conditioning regimens. [31][32][33][34][35] Immunosuppressant therapy is tapered rapidly and DLI commenced early (1-6 months) and then stopped when a degree of GvHD is present or when a set cell dose is reached.…”
Section: Predicting and Preventing Relapsementioning
confidence: 99%
“…The group included adults and children and the donor was an HLA-identical sibling in 24, unrelated donor in 14 (3 mismatched) and 1 was a mismatched relative. The majority 34 received a myeloablative transplant as the first procedure, 59% including TCD in the protocol. The second allograft was performed using fludarabine-based RIC in most cases.…”
Section: Donor Leucocyte Infusionsmentioning
confidence: 99%
“…The relatively good results of allogeneic BMT (matched related and MUD) compared with conventional chemotherapy are because of the existence of graft-versusleukemia (GVL) effect, 21,22 in addition to the myeloablation obtained with high-dose radio-chemotherapy. Ph+ ALL patients should therefore be considered for allogeneic stem cell transplantation in first CR.…”
Section: Mud Transplantationmentioning
confidence: 99%
“…Several reports have shown a strong association between the existence of post-transplant GVHD and a lower relapse risk 22,64 Therefore, donor lymphocyte infusion has been suggested to augment this antileukemic effect even further. 21,65 Although response following DLI in patients with relapsed ALL is considered to be disappointing, [66][67][68] some recent publications suggest DLI to be effective in some of the patients. 21,65 Schaap et al 21 reported a significant reduction in relapse rate in ALL patients who had an allogeneic BMT followed by pre-emptive DLI therapy.…”
Section: Donor Lymphocyte Infusionmentioning
confidence: 99%
“…8,9 This approach appears to be effective for patients with CML 10 and may also have a role for patients with acute leukemia. 11 In one trial that included 82 patients with a variety of diseases, pre-emptive DLI resulted in improved 3-year DFS though was complicated by unacceptable GVHD when given at 0.7  10 8 CD3 cells/kg; only eight of 25 patients who received 0.1 m  10 8 CD3 cells/kg developed grade I-II acute GVHD. 11 In CML, other successful approaches to minimize GVHD have included the use of low-dose DLI with gradual dose escalation, 12 depletion of CD8-positive cells from the donor product, 13,14 and the use of irradiated (and hence inactivated) DLI.…”
mentioning
confidence: 99%